Nodular lesion with polymorphous vascular pattern - Virgínia Coelho de Sousa; André Oliveira (Mattioli1885, 2017)
Dermatofibroma (DF) is one of the most common skin neoplasms seen by dermatologists.  Out of the various histopathological subtypes of DF, the atrophic variant is considered rare. Clinical and dermoscopic diagnosis of DF is straightforward in most cases. However, deeply atypical clinical and dermoscopic presentations can simulate other benign and malignant tumors. We present a case of atrophic DF, describing its dermoscopic features and the correlation with histopathology.